74‐3: Study on Mechanical Behavior and Effect of Adhesive Layers in Foldable AMOLED Display by Finite Element Analysis. Issue 1 (29th May 2019) - Cheng, Aries; Chen, Yuanyuan; Jin, Jian; Su, Tsungyi
Abstract : In this study, the film stacks of foldable AMOLED display are analyzed and designed by finite element analysis (FEA). Controlling the position of neutral plane is one of the key designs for foldable AMOLED display. However, the use of optically clear adhesives (OCA) has a particular effect on the prediction of neutral plane. In the FEA, traction‐separation law is chosen to describe the mechanical behavior of adhesives; also the material parameters and failure strength of adhesives are obtained by basic material tests in advance. A 5.99‐inch WQHD prototype foldable AMOLED display has been successfully folded more than 100, 000 times in dynamic and static mixing at 3mm inward folding radius without damages.